PROBLEMATIKA PENGHITUNGAN DAN PEMBAGIAN WARISAN PADA KELUARGA MUSLIM - Zuhdi, Muhammad (Universitas Islam Negeri Raden Fatah Palembang, 2017)
The complicated problem that Muslim families oftenexperience when dividing their inheritance, when among the heirswants to master their own inheritance. They feel more entitled thanothers, thus harming other heirs. The emergence of hostilities, disputesbetween one another. Most of the solutions offered in the case ofinheritance division are by dividing equally. There are also those whoresolve it in court or other efforts. Islamic teachings offer solving thisinheritance problem, so that the brotherhood in the family is wellpreserved. That way is back to the Qur'an and the Sunnah of theProphet. This paper focuses on the study of counting calculations anddivision of inheritance in Muslim families.